New Insight into the Deep Structure of Antarctic Peninsula Continental Margin by Methods of 2d Gravity/Magnetic Modelling and 3d Seismic Tomography - Yegorova, T.; Bakhmutov, V.; Gobarenko, V.; Lyashchuk, A. (Український антарктичний журнал, 2009)
The Antarctic Peninsula, one of several terrains of Western Antarctica, is a Mesozoic magmatic arc at the southeastern Pacific margin. In order to investigate the structure of the crust and uppermost mantle of Antarctic Peninsula continental margin we have developed joint geophysical models by 2D gravity and magnetic modelling along two most representative and lengthy seismic refraction lines, acquired by Polish Academy of Sciences in 1980-1990th.